Videoassisted mitral valve replacement - Alexander Candeaux; Antonio de Arazoza Hernández; Aylen Pérez Barreda; Fausto Rodríguez Salgueiro; Osvaldo Valdés Dupeirón; Miguel Ángel Carrasco Molina (ECIMED, 2012)
The surgery of the mitral valve has been a great challenge since the beginnings of the cardiovascular surgery, the surgical options to board this valverange from percutaneous methods to dilate it, till the substitution for a prosthetic heart valve through a median sternotomy. In our country the mitral valvesubstitution is done through the median sternotomy and right thoracotomy methods. The case of a 56 year-old feminine patient, with antecedents ofsevere, symptomatic mitral insufficiency, with indication of mitral valve substitution that was intervened with a novel technique of minimum access videoassisted,is presented.